A journey through the history of commodity derivatives markets and the political economy of (de)regulation - Bernardina Algieri (University of Bonn, Center for Development Research (ZEF), 2018)
The present study examines the dynamics and regulatory regimes of commodity derivatives markets through time. The historical perspective allows to identify the reasons behind the use of derivatives and the impact of changing rules on financial systems. It further permits to highlight the weaknesses and the strengths of derivatives markets and provides valuable lessons to tackle challenges, replicate practices, and prevent failures. The analysis shows that derivatives markets have a long history and have facilitated trading across time and geographical areas. The results of a quasi-experiment conducted for Japan and the US reveal that commodity price fluctuations were higher before the establishment of futures markets. The analysis further indicates that the unprecedented inflow of liquidity in derivatives markets was mainly facilitated by the deregulation policies adopted in the US, EU and elsewhere and was intensified by an increasing interest of investors in alternative asset classes. In the new millennium many product innovations flooded the market, reducing transparency and increasing market uncertainty. The study indicates that improved data quality and quantity are necessary conditions to enhance the understanding of derivatives markets. In addition, a sound legal and financial system is a must for thriving financial markets. Such a system creates a framework of checks and balances for the market, it contributes significantly to meaningful regulations and vibrant policies and helps to prevent or eradicate market manipulations.
Keywords: N20; G28; G15; Q14; 330; derivatives markets; history; regulatory regimes